2012
DOI: 10.1016/j.rmed.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter β2-agonist purchase versus script: A cross-sectional study

Abstract: Purchase of SABA without prescription was not associated with worse asthma outcomes in Australia. Although many patients reported symptoms of asthma, this did not appear to be associated with reported adherence to anti-inflammatory asthma medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…(Braido 2013) Another study reported that obtaining SABAs without a prescription did not lead to poorer asthma control; instead it supported the claim that OTC availability of these medications benefits asthma patients. (Douglass et al 2012) On the other hand, other studies reported that OTC asthma medicines have resulted in under-treatment and less consultation with doctors, (Gibson et al 1993) and assessment and counseling provided by pharmacists or other pharmacy staff was less than the optimal. (Schneider et al 2009) However, this inadequate counseling may have resulted from unwillingness of patients with long term chronic diseases to discuss with healthcare professionals what they believed they already know.…”
Section: Discussionmentioning
confidence: 99%
“…(Braido 2013) Another study reported that obtaining SABAs without a prescription did not lead to poorer asthma control; instead it supported the claim that OTC availability of these medications benefits asthma patients. (Douglass et al 2012) On the other hand, other studies reported that OTC asthma medicines have resulted in under-treatment and less consultation with doctors, (Gibson et al 1993) and assessment and counseling provided by pharmacists or other pharmacy staff was less than the optimal. (Schneider et al 2009) However, this inadequate counseling may have resulted from unwillingness of patients with long term chronic diseases to discuss with healthcare professionals what they believed they already know.…”
Section: Discussionmentioning
confidence: 99%
“…(Braido 2013) Another study reported that obtaining SABAs without a prescription did not lead to poorer asthma control; instead it supported the claim that OTC availability of these medications benefits patients with asthma . (Douglass et al 2012) . Moreover, the availability of some medications to treat asthma such as (SABAs) as a Pharmacist Only medications in Australia, that do not require a prescription, may have increased participants' confidence to obtain more asthma medications without a valid prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitatively, patients cited low perceived value of physician visits, greater convenience, and greater sense of control as reasons for nonprescription purchase (49). More recently, 40% of quick reliever purchasers obtained their medication without a prescription (50). Nonprescription purchasers tended to be younger (39 vs. 54 yr) and use controller medications less frequently (50% vs. 65%) than prescription purchasers.…”
Section: Nonprescription Use Of Quick Reliever Medications In Australiamentioning
confidence: 99%